Production of phytodetritus by a coral reef sponge increases from shallow to mesophotic depths - Michael P. Lesser; Keir J. Macartney; Marc Slattery (Limnology and Oceanography, 2023)
On Caribbean coral reefs, sponges are important members of the benthic community and have an important role in consuming particulate organic matter (POM) and dissolved organic matter (DOM), with the subsequent production of detritus that is then shunted into a process now referred to as the “sponge‐loop.” An emergent species of sponge commonly found on Caribbean coral reefs, Agelas tubulata , increases in size and growth rate from shallow ( A . tubulata depends largely on heterotrophy across shallow to mesophotic depths and has been shown to utilize detritus on shallow reefs. However, detritus production by A . tubulata on shallow and mesophotic coral reefs has not been previously reported. Here we show, using flow cytometry, that sponge detritus includes a previously unquantified component, phytodetritus. Sponge phytodetritus production was shown experimentally to be greater in sponges from mesophotic depths compared to sponges from shallow coral reefs. Additionally, the size range of this phytodetritus corresponds to the size range of autotrophic picoplankton, primarily prochlorophytes, known to be an important food source for filter‐feeding sponges. Given the known lability of phytodetritus, compared to other more recalcitrant components of the detrital pool, its role in the food web of mesophotic communities combined with the increased availability of live POM, may be an underappreciated component of mesophotic community carbon and nitrogen flow.

Trophic ecology of Caribbean sponges in the mesophotic zone - Keir J. Macartney; Marc Slattery; Michael P. Lesser (Limnology and Oceanography, 2021)
Sponges are a crucial component of Caribbean coral reef ecosystem structure and function. In the Caribbean, many sponges show a predictable increase in percent cover or abundance as depth increases from shallow ( Xestospongia muta , Agelas tubulata , and Plakortis angulospiculatus , and use stable isotope analyses to determine whether shifts in trophic resource utilization along a shallow to mesophotic gradient occurred. Ecological surveys show that all target sponges significantly increase in percent cover as depth increases. Using bulk stable isotope analysis, we show that as depth increases there are increases in the δ 13 C and δ 15 N values, reflecting that all sponges consumed more heterotrophic picoplankton, with low C:N ratios in the mesophotic zone. However, compound‐specific isotope analysis of amino acids (CSIA‐AA) shows that there are species‐specific increases in δ 13 C AA and δ 15 N AA values. Xestospongia muta and P. angulospiculatus showed a reduced reliance on photoautotrophic resources as depth increased, while A. tubulata appears to rely on heterotrophy at all depths. The δ 13 C AA and δ 15 N AA values of these sponges also reflect species‐specific patterns of host utilization of both POM and dissolved organic matter (DOM), its subsequent re‐synthesis, and translocation, by their microbiomes.

Depth‐dependent detritus production in the sponge, Halisarca caerulea - Michael P. Lesser; Benjamin Mueller; M. Sabrina Pankey; Keir J. Macartney; Marc Slattery; Jasper M. de Goeij (Limnology and Oceanography, 2020)
Sponges are important ecological and functional components of coral reefs. Recently, a new hypothesis about the functional ecology of sponges in organic matter recycling pathways, the sponge‐loop hypothesis, in which dissolved and particulate organic matter is taken up by sponges and shunted to higher trophic levels as detritus, has been proposed and demonstrated for shallow ( Halisarca caerulea from water depths of 10 and 50 m. Detritus production was significantly lower in mesophotic sponges compared to shallow samples of H. caerulea . Additionally, detritus production rates in transplanted sponges moved in the direction of rates observed for resident conspecifics. The microbiome of these sponge populations was also significantly different between shallow and mesophotic depths, and the microbial communities of the transplanted sponges also shifted in the direction of their new depth in 10 d largely driven by changes in Oxyphotobacteria , Acidimicrobiia , Nitrososphaeria , Nitrospira , Deltaproteobacteria , and Dadabacteriia . This occurred in an environment where the availability of both dissolved and particulate trophic resources changed significantly across the shallow to mesophotic depth gradient where these sponge populations were found. These results suggest that changes in sponge detritus production are primarily driven by differential quality and quantity of trophic resources, as well as their utilization by the sponge host, and its microbiome, along the shallow to mesophotic depth gradient.

Will coral reef sponges be winners in the Anthropocene? - Michael P. Lesser; Marc Slattery (Global Change Biology, 2020)
Recent observations have shown that increases in climate change‐related coral mortality cause changes in shallow coral reef community structure through phase shifts to alternative taxa. As a result, sponges have emerged as a potential candidate taxon to become a “winner,” and therefore a numerically and functionally dominant member of many coral reef communities. But, in order for this to occur, there must be sufficient trophic resources to support larger populations of these active filter‐feeding organisms. Globally, climate change is causing an increase in sea surface temperatures (SSTs) and a decrease in salinity, which can lead to an intensification in the stratification of shallow nearshore waters (0–200 m), that affects both the mixed layer depth (MLD) and the strength and duration of internal waves. Specifically, climate change‐driven increases in SSTs for tropical waters are predicted to cause increased stratification, and more stabilized surface waters. This causes a shallowing of the MLD which prevents nutrients from reaching the euphotic zone, and is predicted to decrease net primary production (NPP) up to 20% by the end of the century. Lower NPP would subsequently affect multiple trophic levels, including shallow benthic filter‐feeding communities, as the coupling between water column productivity and the benthos weakens. We argue here that sponge populations may actually be constrained, rather than promoted, by climate change due to decreases in their primary trophic resources, caused by bottom‐up forcing, secondary to physical changes in the water column (i.e., stratification and changes in the MLD resulting in lower nutrients and NPP). As a result, we predict sponge‐dominated tropical reefs will be rare, or short‐lived, if they occur at all into the future in the Anthropocene.

Global community breaks at 60 m on mesophotic coral reefs - Michael P. Lesser; Marc Slattery; Jack H. Laverick; Keir J. Macartney; Tom C. Bridge (Global Ecology and Biogeography, 2019)
Aim Mesophotic coral ecosystems (MCEs) are unique communities that support a high proportion of depth‐endemic species distinct from shallow‐water coral reefs. However, there is currently little consensus on the boundaries between shallow and mesophotic coral reefs and between upper versus lower MCEs because studies of these communities are often site specific. Here, we examine the ecological evidence for community breaks, defined here as species loss, in fish and benthic taxa between shallow reefs and MCEs globally. Location Global MCEs. Time period 1973–2017. Major taxa studied Macrophytes, Porifera, Scleractinia, Hydrozoa, Octocorallia, Antipatharia and teleost fishes. Methods We used random‐effects models and breakpoint analyses on presence/absence data to identify regions of higher than expected species loss along a depth gradient of 1–69 m, based on a meta‐analysis of 26 studies spanning diverse photoautotrophic and heterotrophic taxa. We then investigated the extent to which points of high faunal turnover can be explained by environmental factors, including light, temperature and nutrient availability. Results We found evidence for a community break, indicated by a significant loss of shallow‐water taxa, at ~ 60 m across several taxonomically and functionally diverse benthic groups and geographical regions. The breakpoint in benthic composition is best explained by decreasing light, which is correlated with the optical depths between 10 and 1% of surface irradiance. A concurrent shift in the availability of nutrients, both dissolved and particulate organic matter, and a shift from photoautotroph to heterotroph‐dominated assemblages also occurs at ~ 60 m depth. Main conclusions We found evidence for global community breaks across multiple benthic taxa at ~ 60 m depth, indicative of distinct community transitions between shallow and mesophotic coral ecosystems. Changes in the underwater light environment and the availability of trophic resources along the depth gradient are the most parsimonious explanations for the observed patterns.

Phylogenetic signature of light and thermal stress for the endosymbiotic dinoflagellates of corals (Family Symbiodiniaceae) - Michael P. Lesser (Limnology and Oceanography, 2019)
Coral reefs around the world have been affected by a climate‐change induced phenomenon known as “coral bleaching,” which is caused by the interaction between high irradiance and elevated seawater temperatures, and involves the mass expulsion of Symbiodiniaceae from anemones, sponges, and corals. The primary drivers of this phenomenon are the inherent genetic variability in the Family Symbiodiniaceae, and the variability in the abiotic environment for variables such as irradiance and temperature. Recent experiments have either disregarded the important interactive role of irradiance or have suggested that photooxidative stress is not a prerequisite for coral bleaching because certain reactive oxygen species (ROS) can be produced in the dark. Here, fluorescent probes are used as proxies for the relative concentration of ROS in different genera of cultured Symbiodiniaceae under varying thermal and light conditions. The results show that taxon‐specific patterns of the concentration of ROS are observed but that all genera tested produced significantly greater amounts of superoxide radicals and hydrogen peroxide, compared to singlet oxygen, when exposed to high light and thermal stress. These results are contextualized in relation to the primary drivers of ROS production and the photo‐physiological basis for differences in ROS production that may then be correlated with symbiont driven coral bleaching.

Environmental drivers of microbial community shifts in the giant barrel sponge, X estospongia muta , over a shallow to mesophotic depth gradient - Kathleen M. Morrow; Cara L. Fiore; Michael P. Lesser (Environmental Microbiology, 2016)
Summary The giant barrel sponge, X estospongia muta , is a high microbial abundance sponge found on Caribbean coral reefs along shallow to mesophotic depth gradients where multiple abiotic factors change with depth. Sponges were collected along a depth gradient at L ittle C ayman ( LC ) and Lee Stocking Island ( LSI ), and the microbiome of these samples was analysed using 16 S r RNA amplicon sequencing. Statistically significant shifts in community structure and dissimilarity (∼ 40%) were detected from 10 to 90 m in LC sponges, but a similar shift was not identified in sponges from 10 to 60 m at LSI (only 17% dissimilar). Additionally, inorganic nutrient levels steadily increased with depth at LSI but not at LC . Based on bulk stable isotopic variability, sponges collected from LC were generally more enriched in 15 N and less enriched in 13 C as depth increased, suggesting a transition from dependency on photoautotrophy to heterotrophy as depth increased. Patterns of stable isotopic enrichment were largely invariant at LSI , which is also reflected in the more stable microbial community along the depth gradient. It appears that environmental factors that change with depth may contribute to differences in X . muta microbial assemblages, demonstrating the importance of contemporaneous environmental sampling in studies of the microbiome of sponges.

Photoacclimatization by the coral Montastraea cavernosa in the mesophotic zone: light, food, and genetics - Michael P. Lesser; Marc Slattery; Michael Stat; Michiko Ojimi; Ruth D. Gates; Andrea Grottoli (Ecology, 2010)
Most studies on coral reefs have focused on shallow reef ( Montastraea cavernosa has a wide depth distribution, and it is one of the most numerous corals at mesophotic depths. Using a range of optical, physiological, and biochemical approaches, the relative dependence on autotrophy vs. heterotrophy was assessed for this coral from 3 to 91 m. These measurements show that the quantum yield of PSII fluorescence increases significantly with depth for M. cavernosa while gross primary productivity decreases with depth. Both morphological and physiological photoacclimatization occurs to a depth of 91 m, and stable isotope data of the host tissues, symbionts, and skeleton reveal a marked decrease in productivity and a sharp transition to heterotrophy between 45 and 61 m. Below these depths, significant changes in the genetic composition of the zooxanthellae community, including genotypes not previously observed, occur and suggest that there is strong selection for zooxanthellae that are suited for survival in the light‐limited environment where mesophotic M. cavernosa are occurring.

Solving cryptogenic histories using host and parasite molecular genetics: the resolution of Littorina littorea 's North American origin - APRIL M. H. BLAKESLEE; JAMES E. BYERS; MICHAEL P. LESSER (Molecular Ecology, 2008)
Even after decades of investigation using multiple sources of evidence, the natural histories of some species remain unclear (i.e. cryptogenic). A key example is Littorina littorea , the most abundant intertidal snail in northeastern North America. Native to Europe, the snail's ecological history in North America has been debated for over 100 years with no definitive resolution. To resolve its cryptogenic status, we used molecular genetics from a novel combination of the snail and a highly associated trematode parasite, Cryptocotyle lingua . Based on mitochondrial sequences of 370 L. littorea and 196 C. lingua individuals, our results demonstrate a significant reduction in genetic diversity in North America vs. Europe, North American haplotypes nested within European haplotypes, and mean divergence estimates of ~500 years ago from Europe for both host and parasite — thus supporting a recent introduction of both host and parasite to North America from Europe. Our study therefore resolves not only a specific cryptogenic history, but it also demonstrates the success of our approach generally and could be used in resolving difficult invasion histories worldwide.

Variation in sunscreen compounds (mycosporine‐like amino acids) for marine species along a gradient of ultraviolet radiation transmission within doubtful sound, New Zealand - Miles D. Lamare; Michael P. Lesser; Mike F. Barker; Thomas M. Barry; Kate B. Schimanski (New Zealand Journal of Marine and Freshwater Research, 2004)
We examined the response of four species of New Zealand marine algae ( Ecklonia radiata, Apophlaea lyallii, Rhodymenia spp., Ulva lactuca ) and a sea urchin ( Evechinus chloroticus ) to spatial variation in ultraviolet radiation (UV‐R) by examining the concentration of UV‐R absorbing compounds known as mycosporine‐like amino acids (MAAs). The purpose was to understand how, and the degree to which, local marine species could potentially respond to any future increases in incident UV‐R in the New Zealand marine environment. The research was undertaken in Doubtful Sound, where we observed a gradient of water column UV‐R transmission along the 40 km length of the fiord. We examined spatial differences in MAAs along the UV‐B gradient in the macrophytes and temporal changes in MAAs in sea urchin gonads. Among the algae, thallus MAA concentrations (nmol mg –1 protein) ranged from 12.5 to 87.8 in E. radiata , from 433.1 to 1446.4 in A. lyallii , 12.7 to 103.4 in Rhodymenia spp., but were not detected in U. lactuca . For E. chloroticus , gonadal MAA concentrations ranged from 83.9 to 224.3 nmol mg –1 protein spatially, and over the year from 1.85 to 14.12 nmol mg –1 dry weight (DW) depending on site and gametogenic cycle. Laboratory manipulations indicated that concentrations of MAAs in E. chloroticus gonads and eggs are influenced by diet. MAA concentration could be correlated with UV‐B intensities in two of the algal species. E. chloroticus MAA concentrations could also be correlated with UV‐B transmission, which we concluded was a reflection of the greater ingestion and accumulation of MAA‐rich macrophytes at those sites where higher ambient UV‐R induced greater MAA concentrations to occur in the algae. Given this, we suggest that one response of marine species to increases in UV‐B would be an increase in the synthesis and/or accumulation of MAAs for photoautotrophs and a dietary accumulation of those MAAs in E. chloroticus , an important herbivore in this system.

Transmission of ultraviolet radiation through the Antarctic annual sea ice and its biological effects on sea urchin embryos - Michael P. Lesser; Miles D. Lamare; Michael F. Barker (Limnology and Oceanography, 2004)
Stratospheric ozone depletion over Antarctica is expected to continue for the next 50 years, with increases in ecologically damaging ultraviolet radiation (UVR: 290–400 nm), specifically the ultraviolet‐B (UVB: 290–320 nm) portion of the spectrum. Most of coastal Antarctica is covered with 2–3 m of annual sea ice during the occurrence of the “ozone hole.” This physical barrier to UVR transmission has long been assumed to provide complete protection from the biologically damaging effects of UVR, especially for the planktonic developmental stages of the benthic invertebrate fauna. We found that short‐wavelength UVB (down to 304 nm) is transmitted through the Austral spring annual ice of McMurdo Sound, and causes significant mortality and DNA damage in the embryos of the sea urchin Sterechinus neumayeri . Although mortality of sea urchin embryos has been reported for the open waters of the Antarctic, this is the first documentation of mortality and DNA damage for embryos under the annual sea ice. The degree of mortality and DNA damage was dependent on both year and depth, with higher mortality and DNA damage at 1 m depth below the ice compared to 3 m and 5 m. Greater DNA damage occurred in 2003 compared to 2002 despite the thicker annual ice (3.1 m vs. 2.5 m). Although the thickness of the annual ice was greater, the severity of the ozone hole, 230 Dobson units (DU) versus 320 DU, and the ratio of UVB to visible radiation was greater in 2003. Embryo and larval mortality from exposure to UVR under the annual ice should be considered as another abiotic factor potentially affecting the temporally episodic recruitment of invertebrates that occur in this benthic ecosystem.

Green‐fluorescent proteins in Caribbean corals - Charles H. Mazel; Michael P. Lesser; Maxim Y. Gorbunov; Thomas M. Barry; Julianne H. Farrell; Kevin D. Wyman; Paul G. Falkowski (Limnology and Oceanography, 2003)
Fluorescent pigments in several Indo‐Pacific and Caribbean anthozoans have recently been identified as proteins related to the Green‐fluorescent protein (GFP) of the hydromedusa Aequorea victoria . Here we show that GFP is widely distributed in many Caribbean species. The fluorescence excitation and emission spectra for the pigment are similar to those reported elsewhere for coral and noncoral GFP and the fluorescence quantum yield is estimated to be 35%. Spectral and molecular characterization of the isolated protein clearly show it to be GFP, and laboratory and in situ fluorescence measurements and Western blot analysis show that it is widespread. Bathymetric studies of GFP content using Western blots for the ecologically important congeneric corals Montastraea faveolata and Montastraea cavernosa show that there is no significant correlation between depth and GFP concentration. Nucleotide sequence data of GFP from M. faveolata and M. cavernosa show 88.2% sequence homology with each other and 46.4% homology with A. victoria GFP, whereas the percent homology with A. victoria at the amino acid level was 31.1 and 28.4% for M. cavernosa and M. faveolata , respectively, and 82.7% with each other. Measurements of reflectance and of the excitation spectrum for chlorophyll fluorescence in GFP‐containing corals indicate that GFP absorption, emission, and reflection have negligible impact on the level of solar radiation reaching the zooxanthellae and therefore play no role in coral photosynthesis by either addition or removal of photons.

High‐resolution determination of coral reef bottom cover from multispectral fluorescence laser line scan imagery - Charles H. Mazel; Michael P. Strand; Michael P. Lesser; Michael P. Crosby; Bryan Coles; Andrew J. Nevis (Limnology and Oceanography, 2003)
A prototype in‐water laser line‐scanning multispectral fluorescence imaging system was evaluated for its ability to provide data that could be used to determine the quantitative distribution and abundance of various functional groups on coral reefs. The system collected fluorescence imagery in three spectral bands with 1 cm 2 resolution at sites in Florida and the Bahamas. Fluorescence excitation was at 488 nm, and imagery was collected in emission bands centered at 520, 580, and 685 nm. Ground truth data on bottom cover was collected by divers using conventional line transect and photographic quadrat methods. A set of classification rules based on the relative signal levels in the three fluorescence channels was developed to assign the image pixels to functional groups. Once the image was classified, percent cover data for the groups were computed for the full image and for subsets of the image chosen to simulate line transect, grid survey, and photographic quadrat surveys. The statistics of percent cover of various bottom types derived from the fluorescence image compared favorably with those determined by diver survey techniques. The results demonstrate that fluorescence imaging has the long‐term potential to provide coverage of large spatial areas of coral reefs at high resolution, with automated classification and quantification of functional groups in the image.

Photosynthesis and photoprotection in symbiotic corals - Maxim Y. Gorbunov; Zbigniew S. Kolber; Michael P. Lesser; Paul G. Falkowski (Limnology and Oceanography, 2001)
In zooxanthellate corals, excess excitation energy can be dissipated as heat (nonphotochemical quenching), thereby providing protection against oxidative damage by supraoptimal light in shallow reefs. To identify and quantify the photoprotective mechanisms, we studied the diel variability of chlorophyll fluorescence yields and photosynthetic parameters in situ in corals, using moored and SCUBA‐based fast‐repetition‐rate fluorometers. The results reveal that nonphotochemical quenching is triggered prior to saturation of photosynthetic electron transport by down‐regulation of the reaction centers of Photosystem II (PSII). This process dissipates up to 80% of the excitation energy. On a sunny day in shallow waters, the daily integrated flux of photons absorbed, and subsequently dissipated as heat, is ~4 times that used for photosynthesis. Fluorescence quenching is further accompanied by a slight reduction in the functional absorption cross section for PSII that results from thermal dissipation of excitation energy in the light‐harvesting antennae. These two processes are highly dynamic and adjust to irradiance changes on timescales consistent with the passage of clouds across the sky. Under supraoptimal irradiance, however, up to 30% of PSII reaction centers become photoinhibited, and these are repaired only after several hours of low irradiance. In shallow corals, between 10% and 20% of the reactions centers are chronically photoinhibited and appear to remain permanently nonfunctional throughout the year. Our results establish, for the first time, the suite of biophysical mechanisms that optimize photosynthesis while simultaneously providing photoprotection in symbiotic corals in situ.

The effects of UV radiation in the marine environment - Michael P. Lesser (Limnology and Oceanography, 2001)

UV‐absorbing compounds in the coral Pocillopora damicornis : Interactive effects of UV radiation, photosynthetically active radiation, and water flow - Paul L. Jokiel; Michael P. Lesser; Michael E. Ondrusek (Limnology and Oceanography, 1997)
A direct relationship exists between irradiance of solar ultraviolet (UV) radiation and concentration of UV‐absorbing compounds, know as mycosporine‐like amino acids (MAAs), in the Hawaiian reef coral Pocillopora damicornis. However, MAA concentration is also influenced by flow regime and the irradiance of photosynthetically active radiation (PAR). High irradiances of UV radiation in reef environments are correlated with high PAR and high water velocity, because all three parameters diminish exponentially with increased depth. This correlation can also be found along horizontal gradients on reefs. The clearest water is typically found on outer reefs growing in oceanic water. These ocean reefs typically experience high water velocities due to ocean swell when compared to the more turbid lagoon reefs exposed only to small wind‐driven waves. Flow‐modulated photosynthetic rate seems to be a major factor affecting the observed changes in MAA concentration when P. damicornis is grown under different flow regimes and identical irradiances of UV and PAR radiation. High PAR and high water velocity significantly enhance the effect of increased UV radiation on MAA concentration.